High-frequency stimulation of the subthalamic nucleus inhibits the firing of juxtacellular labelled 5-HT-containing neurones. - Hartung, H; Tan, S; Steinbusch, H; Temel, Y; Sharp, T (2011)
High-frequency stimulation (HFS) of the subthalamic nucleus (STN) is an established neurosurgical therapy for movement disability in advanced Parkinson's disease (PD), but some patients experience psychiatric side-effects like depression. In a previous electrophysiological study, we observed that HFS of the STN inhibited a population of neurones in the rat dorsal raphe nucleus (DRN), with firing properties characteristic of 5-HT neurones. The present study extended these findings to a second population of neurones, and combined extracellular recording with juxtacellular-labelling to investigate the chemical identity of the neurones affected by HFS. Bilateral HFS (130 Hz, 100-200 μA, 5 min) of the STN inhibited (26.0±2.9%) the firing of 37/74 DRN neurones displaying a slow, regular firing pattern. Slower firing neurones were more strongly inhibited than those firing faster. Importantly, 10 inhibited DRN neurones were juxtacellular-labelled with neurobiotin, and all neurones contained 5-HT as shown by post-mortem 5-HT immunocytochemistry. A minority of slow firing DRN neurones (18/74) were activated by STN HFS (37.9±8.3%) which was not observed previously. Of these neurones, three were juxtacellular-labelled and one was 5-HT immunopositive. Also a small number of DRN neurones (19/74) did not respond to HFS, four of which were juxtacellular-labelled and all contained 5-HT. These data show that individual chemically-identified 5-HT-containing neurones in the DRN were modulated by STN HFS, and that the majority were inhibited but some were activated and some failed to respond. These data extend previous findings of modulation of the 5-HT system by STN HFS but suggest a destabilisation of the 5-HT system rather than simple inhibition as indicated previously. Although the mechanism is not yet known, such changes may contribute to the psychiatric side-effects of STN stimulation in some PD patients.